On the impact of mode of presentation and age on parsing structurally ambiguous relative clauses - Sarkhosh, Mehdi; Ghaedrahmat, Mehdi (East European Journal of Psycholinguistics, 2023)
The relative clause Attachment preferences of female Persian learners of English were investigated regarding their age and modes of presentation (online/offline and holistic/segmented). 50 female native speakers of Persian ranging in age from 15 to 25 participated in the study. The instruments used in the present research included two tests of ambiguous sentences: 1) a grammaticality judgment test, and 2) the main test which was presented in three separate forms: a) Offline, b) online complete presentation (timed) and c) online segment by segment sentence (Self-Paced). This study used the method employed by Kim and Christianson (2013) for determining the attachment preferences of the participants. The results revealed that the participants’ age affected the attachment preferences significantly in that adolescents had a clear determiner phrase 1 preference. There was also a statistically significant difference among the three modes of presenting the materials. The findings revealed that learners transferred their attachment strategies from their mother tongue to English, which provided support for transfer hypothesis. The research findings on whether L2 learners can achieve native like patterns of ambiguity resolution is still less than conclusive and findings seem to suggest that L2 learners apply parsing strategies which are less automatized than native speakers and even at odds with some studies reporting no transfer of L1 parsing strategies. Language teachers should make their learners cognizant of relative clause attachment preferences in English to avert their transfer of their mother tongue strategies in determining the antecedents of the relative clauses. Disclosure Statement No potential conflict of interest was reported by the authors. * Corresponding author: Mehdi Sarkhosh, 0000-0002-2483-4662 ma.sarkhosh@urmia.ac.ir